The Value of Habitat Complexity and Diversity of Reef Fish Species in Sangiang Island, Bima Regency, West Nusa Tenggra - Rahmat Hidayatullah; Didik Santoso; Abdul Syukur (Jurnal Biologi Tropis, 2020)
Coral reef ecosystems in the marine environment have a vital role, especially in providing habitat for the diversity of commercial and non-commercial fish species. This study aims to assess the species richness of coral reef fish based on the complexity of the habitat of Sangiang Island, Bima Regency. The data collection method used Underwater Visual Census on the belt transect, and the habitat complexity value is determined by the chain intercept transect method. Data analysis used Shannon-Wiener Index Diversity (H '), Abundance (Ki), and Habitat complexity (C). Next is a simple regression analysis between habitat complexity as the independent variable and fish abundance as the dependent variable. In this study, 106 species were found and covering 24 families. The three fish families, Pomacentridae, Labridae, and Lutjanidae, are the most dominant of the other families. Meanwhile, the diversity index ranged from 1.874-2.753 with an average value of ÃÂ± SD 2.35 ÃÂ± 0.317, and the abundance value ranged from 0.774-2.528 individuals/m2 with an average value of ÃÂ± SD 1.505 individuals / m2 ÃÂ± 0.745. Furthermore, the analysis showed that hÃÂ¡bitate complexity had a significant effect on fish abundance. The coefficient of determination (R2) of 80% can explain the relationship of habitat complexity to fish abundance in the study location. This study concludes that coral reef habitat complexity is a determining factor for the level of fish diversity and abundance in the study area. Therefore, the protection of coral habitat is a strategy for the protection of coral reef fish resources.